Bilateral anterior interosseous nerve syndrome with 6-year interval. (15th May 2018) - Tyszkiewicz, Thomas; Atroshi, Isam
Flexor pollicis longus paralysis related to idiopathic anterior interosseous nerve syndrome is well known, but few reports exist on bilateral disease. A 24-year-old man with no personal or family history of neurological disease developed isolated total loss of active flexion of the right thumb's interphalangeal joint after undergoing a wrist arthroscopy. Surgical exploration 5 weeks after onset showed flexor pollicis longus tendon to be intact; anterior interosseous nerve decompression was done with no abnormalities found. Because of persistent paralysis, electromyography was performed showing findings consistent with anterior interosseous nerve syndrome. After 7 months without recovery, the patient underwent tendon transfer. After 6 years, the patient presented with left-sided isolated flexor pollicis longus paralysis and electromyography indicated anterior interosseous nerve syndrome. Examination 9 months after onset showed persistent complete flexor pollicis longus paralysis but by 15 months spontaneous complete recovery had occurred. Anterior interosseous nerve syndrome can occur bilaterally and is likely to resolve completely without intervention but recovery may take longer than a year.